An attachment-based intervention for patients with cardiovascular disease and their partners: A proof-of-concept study - Tulloch, Heather; Johnson, Susan; Demidenko, Natasha; Clyde, Matthew; Bouchard, Karen; Greenman, Paul S (Health psychology, 2021)
Couple distress is associated with cardiovascular disease (CVD) risk factors, whereas support is associated with heart-healthy behaviors and better CVD outcomes. To assess the clinical benefit of the Healing Hearts Together (HHT) intervention, an attachment-based relationship enhancement program for couples in which 1 partner has CVD, on relationship quality, mental health, and quality of life (QoL). Patients from a tertiary cardiac care center and their partners (N = 78; 39 couples) attended the 8-session HHT group. Participants completed validated, self-report questionnaires pre- and postintervention, including the Dyadic Adjustment Scale (DAS), Couple Satisfaction Index (CSI), Hospital Anxiety and Depression Scale (HADS), and the SF-36 (QoL). At intervention completion, participants completed a satisfaction survey. Between-groups comparisons (patient/partner) were examined with analysis of variance. Paired-sample t tests were used to assess changes over time with HHT participation for the complete sample and for patients and partners separately. Many participants reported relationship and psychological distress at baseline. Clinically and statistically significant changes from pre to postintervention were observed for relationship distress (DAS: +7.8 points; p < .001; CSI changes [+3.6] were clinically significant) and depression (-1.8; p < .001), whereas statistically significant changes occurred for anxiety (-1.5; p < .001), and physical (+2.1; p = .047) and mental (+3.3; p < .001) QoL. Patients, but not partners, reported statistically significant changes in QoL-mental component summary. Clinically and statistically significant changes were observed for anxiety for partners, but not patients. The HHT intervention was beneficial for patients' and partners' relationship quality, mental health, and QoL. A larger randomized controlled trial evaluating the impact of this intervention on relationship quality, mental health and QoL is warranted. (PsycInfo Database Record (c) 2022 APA, all rights reserved).